Efeito do enriquecimento ambiental na organização social do papagaio-verdadeiro (Amazona aestiva) mantido em cativeiro - Coppola, Milena Pereira [UNESP] (2015)
The Blue-fronted Amazon parrot is a monogamous species that has social intelligence. However, it is commonly a victim of environmental illegalities and of life in captivity. The goal of this study was to evaluate the social dynamics and behavioral repertoire when males and females of the same species were put together for the first time, with an emphasis on patterns that would validate the social bond between the birds and stereotypical behaviors. 13 captive males and 13 captive females were used, separated in isosexual groups during the first phase, in sexual groups during the second phase and isolated from the group, in pairs and as a couple, during the third phase. The observations were registered daily in the morning, with a recording time of 20 minutes/bird, adding up to 100 minutes of recording/bird/phase. The behavioral analysis were separated in 8 categories, always observing the maintenance of existing pairs and the new social formations when the birds were put together. For statistical analysis the Friedman test was used to compare the percentage of time that was spent doing each behavior between sexes and between phases, using significance values of P>0.05. The social composition in the isosexual phase was composed of 2 pairs of males, 2 pairs of females and three females. In the sexual phase there were 4 pairs of males and 3 pairs of isosexual females and 1 couple. The obtained results suggest that isolating Blue-fronted amazon parrots, even as a couple, does not promote a condition of animal well-being and maintenance of the social bond, as the stereotypical behaviors increased and the affiliative behaviors decreased in this condition. They also showed that the fidelity of the pairs was maintained in birds with dominant aspect, even in a new environmental and social condition